Efektifitas Pembelajaran Matematika Melalui Penerapan Model Learning Cycle Pada Siswa Kelas XI SMA Negeri 6 Surabaya - Wiwid Suryono; Rendi Hadian A. Tamagola; Dina Mayadiana Suwarma; Hersiyati Palayukan; Joni Wilson Sitopu; Baso Intang Sappaile (Journal on Education, 2023)
This study aims to determine the effectiveness of applying the Learning Cycle model in learning mathematics in class XI students of SMA Negeri 6 Surabaya in the odd semester of the 2022/2023 academic year with the experimental unit being class XI IPA 2 with a total of 28 students consisting of 11 boys and 17 woman. This type of research is a pre-experimental study with The One Group Pretest-Posttest Design. The sampling technique in this study was by means of Multistage Sampling. The research instruments used were learning achievement tests, student activity observation sheets, and student response questionnaires. Data analysis used is descriptive analysis and inferential analysis. Analysis of the results of the study showed that: (1) the average score of students' mathematics learning outcomes before the Learning Cycle model was applied was 23.75 and was in a very low category with a standard deviation of 8.204. Meanwhile, the average score of students' mathematics learning outcomes after the model was applied Learning Cycle was 77.21 with a standard deviation of 9.359 where the lowest score was 54 and the highest score was 92. From these results it was found that 25 students or 89.29% achieved individual mastery and 3 students or 10.71% did not achieve individual mastery. This means that classical mastery is achieved with a normalized gain value of 0.70 in the high category. (3) student activity is in the good category. (4) the student response questionnaire shows that the student response to learning through the Learning Cycle model is positive. Based on the results of this study it can be concluded that the application of the Learning Cycle model is effective in learning mathematics in class XI IPA 2 SMA Negeri 6 Surabaya.